Answer:
m = -5, 0
Step-by-step explanation:
Easiest and quickest way to do this is to graph the equation and find where it intersects the x-axis. If not, then use completing the square or quadratic formula to find your roots.
Answer:
Option D is answer.
Step-by-step explanation:
Hey there!
Given;
f(x) = 10/9 X + 11
Let f(X) be "y".
y = (10/9) X + 11
Interchange "X" and "y".
x = (10/9) y + 11
or, 9x = 10y + 99
or, y = (9x-99)/10
Therefore, f'(X) = (9x-99)/10.
<u>Hope</u><u> it</u><u> helps</u><u>!</u>
Answer:
<u>x = -4/3</u>
Step-by-step explanation:
3x + 4 = 0
3x = -4
<u>x = -4/3</u>
Answer:
A
Step-by-step explanation:
4(x+3)+3(5-x)
=4x+12+15-3x
=x+27
Answer:
x = ![\frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)
Step-by-step explanation:
Given
-
=
← factor denominator
-
= ![\frac{4}{x(x+1)}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7Bx%28x%2B1%29%7D)
[ x ≠ 0, x ≠ - 1 as these would make the terms undefined ]
Multiply through by x(x + 1)
4x² - 5(x + 1) = 4
4x² - 5x - 4 = 4 ( subtract 4 from both sides )
4x² - 5x - 9 = 0 ← in standard form
(x + 1)(4x - 9) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 1 = 0 ⇒ x = - 1
4x - 9 = 0 ⇒ 4x = 9 ⇒ x = ![\frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)
However, x ≠ - 1 for reason given above, then
solution is x = ![\frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)